2015
DOI: 10.1111/vcp.12290
|View full text |Cite
|
Sign up to set email alerts
|

Biologic variability and correlation of platelet function testing in healthy dogs

Abstract: Use of population-based RI appears inappropriate for most platelet function tests, and tests poorly correlate with one another. Future studies on biologic variability and correlation of platelet function tests should be performed in dogs with platelet dysfunction and those treated with antiplatelet therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 31 publications
4
30
0
Order By: Relevance
“…Additionally, CV G > CV I for all CAT parameters in the present study shows that thrombin generation among this dog population is variable. This finding is consistent with other studies examining the biological variability of hemostatic tests in dogs, where platelet function tests and TEG had high CV G . The utility of RIs for interpreting CAT can be further examined by calculating the index of individuality, which incorporates CV A , CV I , and CV G as previously reported .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, CV G > CV I for all CAT parameters in the present study shows that thrombin generation among this dog population is variable. This finding is consistent with other studies examining the biological variability of hemostatic tests in dogs, where platelet function tests and TEG had high CV G . The utility of RIs for interpreting CAT can be further examined by calculating the index of individuality, which incorporates CV A , CV I , and CV G as previously reported .…”
Section: Discussionsupporting
confidence: 89%
“…CV A , CV G , and CV I were calculated by dividing their respective variance component by the square root of the log of the mean for any datasets that were log transformed. Maximum imprecision (CV Max ), maximum inaccuracy (B Max ), maximum total error (TE Max ), and indices of individuality, as well as the reference change value (RCV 95% ) were calculated for each variable using previously reported formulas …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in our study, we used the collagen/epinephrine PFA‐100 cartridge to assess drug‐induced platelet dysfunction. The collagen/epinephrine cartridge has a wide reference interval in dogs, and is susceptible to greater biological variation than the collagen/ADP PFA‐100 cartridge . The collagen/ADP cartridge could have detected some changes in platelet function that were not observed with the collagen/epinephrine cartridge, and the collagen/ADP cartridge could be used in future studies to assess the effects of immunosuppressive treatment on platelet function.…”
Section: Discussionmentioning
confidence: 99%
“…No such correlation was observed when ARA was used as the inducer of platelet aggregation in LTA testing. This suggests that the difference between impedance aggregometry and LTA shows different predictive values for various platelet function tests [25, 26]. Several reports have shown that analgesic therapy with NSAIDs have a significant effect on the efficacy of aspirin [10-14].…”
Section: Discussionmentioning
confidence: 99%